Peningkatan Hasil Belajar Mengenai Nilai Kelompok Pencahan Uang Menggunakan Metode Role Play - Irfan, Ahmad Zainul; Mujiburrahman, Mujiburrahman (Program Studi Pendidikan Luar Sekolah, 2025)
Abstract: Learning strategies and media used in the learning process greatly influence students' understanding and competence in mastering the material taught. This study aims to improve the understanding of grade 2 students of SDN Mertak Paok in calculating the value of a group of fractions of money. This research used a classroom action approach implemented in two cycles with the role play method as the main learning strategy. The research subjects consisted of 22 students (15 boys and 7 girls). Data was collected through observation of students' involvement in learning and the results of the final evaluation in the form of a written test. The results showed a significant improvement in students' ability to calculate fractions. Before the action was taken, only 7 students (35%) achieved a score above the KKM (70). In the first cycle it increased to 17 students (77%) and in the second cycle it reached 20 students (91%). The two students who had not reached the KKM consisted of one student with special needs and one student with abilities below the class average. Based on these findings, the role play method proved to be effective in improving the ability of grade 2 students in fractions.Key Words:Â Role Play Method, Money Fractions, Improved UnderstandingÂ Abstrak: Strategi dan media pembelajaran yang digunakan dalam proses belajar sangat berpengaruh terhadap pemahaman dan kompetensi siswa dalam menguasai materi yang diajarkan. Penelitian ini bertujuan untuk meningkatkan pemahaman siswa kelas 2 SDN Mertak Paok dalam menghitung nilai dari sekelompok pecahan uang. Penelitian ini menggunakan pendekatan tindakan kelas yang dilaksanakan dalam dua siklus dengan metode role play sebagai strategi pembelajaran utama. Subjek penelitian terdiri dari 22 siswa (15 laki-laki dan 7 perempuan). Data dikumpulkan melalui observasi keterlibatan siswa dalam pembelajaran dan hasil evaluasi akhir berupa tes tertulis. Hasil penelitian menunjukkan adanya peningkatan signifikan pada kemampuan siswa dalam menghitung pecahan uang. Sebelum dilakukan tindakan, hanya 7 siswa (35%) yang mencapai nilai di atas KKM (70). Pada siklus pertama meningkat menjadi 17 siswa (77%) dan pada siklus kedua mencapai 20 siswa (91%). Dua siswa yang belum mencapai KKM terdiri dari satu siswa berkebutuhan khusus dan satu siswa dengan kemampuan di bawah rata-rata kelas. Berdasarkan temuan tersebut, metode role play terbukti efektif dalam meningkatkan kemampuan siswa kelas 2 dalam materi pecahan uang.Kata Kunci:Â Metode Role Play, Pecahan Uang, Peningkatan Pemahaman